Excitation Transfer between Distant Quantum Dots in Photonic Crystal Waveguide (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have theoretically studied the excitation transfer between distant quantum dots  in a photonic crystal waveguide. Due to Anderson localization of disordered  position and size of the photonic crystal holes was found to have a highly nontrivial  effect on the interaction. We have simulated realistic systems with different  magnitudes of the disorder and showed that while localization indeed has a  profound effect on both range and magnitude of the dot-dot excitation transfer rate  at several μm distance. The average excitation transfer rate was found to be larger  than 10eV at distance on the order of 10m . The transfer time to this corresponded  was on the order of 10 ps, close to the single qubit operation time and much shorter  than the decoherence time measured. The obtained results were found in good  agreement with previous results.